2015
DOI: 10.1167/iovs.15-17190
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure–Lowering Activity of NCX 470, a Novel Nitric Oxide–Donating Bimatoprost in Preclinical Models

Abstract: PURPOSE. The prostaglandin F2alpha (PGF2a) analogue bimatoprost lowers intraocular pressure (IOP) by increasing uveoscleral outflow at doses shown to elicit redness of the eye. With the aim to enhance the IOP-lowering effect of bimatoprost we studied NCX 470, a dual-acting compound combining bimatoprost with nitric oxide (NO) known to mainly act via relaxation of trabecular meshwork and Schlemm's canal.METHODS. New Zealand white rabbits with transient hypertonic saline-induced IOP elevation (tOHT-rabbits), cyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 26 publications
(47 reference statements)
0
35
0
1
Order By: Relevance
“…Moreover, enhanced vasodilatation, anti‐inflammatory effects and antiplatelet activity have been attributed to NO making this class of molecules particularly interesting as impaired ocular blood flow and inflammation seem to also contribute to glaucoma progression (Resch et al ., ; Costa et al ., ). Various NO‐donating PGs have been described in recent years for their enhanced IOP‐lowering activity in animal models of ocular hypertension and glaucoma compared with standard of care treatments (Borghi et al ., ; Impagnatiello et al ., ; Krauss et al ., ; Impagnatiello et al ., ). Among others, LBN, a compound discovered at Nicox and later licensed by Bausch + Lomb, has been advanced through phase 3 and recently received FDA approval for the reduction of IOP in patients with open‐angle glaucoma and ocular hypertension (Vyzulta™, LBN ophthalmic solution, 0.024%,).…”
Section: Pg Analogues As Ocular Hypotensive Agentsmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, enhanced vasodilatation, anti‐inflammatory effects and antiplatelet activity have been attributed to NO making this class of molecules particularly interesting as impaired ocular blood flow and inflammation seem to also contribute to glaucoma progression (Resch et al ., ; Costa et al ., ). Various NO‐donating PGs have been described in recent years for their enhanced IOP‐lowering activity in animal models of ocular hypertension and glaucoma compared with standard of care treatments (Borghi et al ., ; Impagnatiello et al ., ; Krauss et al ., ; Impagnatiello et al ., ). Among others, LBN, a compound discovered at Nicox and later licensed by Bausch + Lomb, has been advanced through phase 3 and recently received FDA approval for the reduction of IOP in patients with open‐angle glaucoma and ocular hypertension (Vyzulta™, LBN ophthalmic solution, 0.024%,).…”
Section: Pg Analogues As Ocular Hypotensive Agentsmentioning
confidence: 97%
“…Nonclinical pharmacological studies have demonstrated that the IOP‐lowering efficacy of NCX 470 is greater than that of equimolar doses of bimatoprost in well‐established animal models of glaucoma and ocular hypertension. In particular, NCX 470 was shown to lower IOP in transient ocular hypertensive rabbits (previously shown to respond poorly to FP receptor agonists, Borghi et al ., ) probably by inducing the release of NO (Impagnatiello et al ., ). Additionally, NCX 470 0.042% lowered IOP more effectively than equimolar doses of bimatoprost (0.03%) in ocular normotensive dogs (Figure A, Impagnatiello et al ., ) and in laser‐induced ocular hypertensive non‐human primates (Figure B, Impagnatiello et al ., ).…”
Section: Pg Analogues As Ocular Hypotensive Agentsmentioning
confidence: 97%
See 1 more Smart Citation
“…The effectiveness of several IOP-lowering therapies that focus on the mechanisms underlying ECM turnover and cell stiffness has already been successfully demonstrated. These include adenosine A1 receptor agonists [3945], nitric oxide donors [12, 4648], Rho Kinase inhibitors [49] and actin depolymerizers (Tables 1, 2) [23, 25, 26, 50–53]. …”
Section: Targeting Schlemm’s Canal To Reduce Iopmentioning
confidence: 99%
“…In a more recent study, Impagnatiello et al [48] compared the IOP-lowering activity of NCX 470, a novel NO-donating bimatoprost, with equivalent dosage of bimatoprost in ocular hypertensive rabbits, ocular normotensive dogs, and hypertensive non-human primates. This novel compound was effective in lowering IOP in all 3 animal models, and a repeated daily dosing of NCX 470 in dogs resulted in sustained IOP-lowering activity over time.…”
Section: Targeting Schlemm’s Canal To Reduce Iopmentioning
confidence: 99%